Online circular contrast perimetry: The normative database of an Asian population - Tung, Hoang Thanh; Tung, Mai Quoc; Dung, Pham Thi; Xuan, Nguyen Thi; Duc Anh, Nguyen; Diu, Vu Thi; Hien, Hoang Thi; Franzco, Simon Skalicky (Tạp chí Nghiên cứu Y học, 2024)
This study compared results of online circular contrast perimetry (OCCP) versus standard automated perimetry (SAP) in clinic, as well as clinic OCCP versus home OCCP in a normal Asian population. Healthy participants underwent a comprehensive ocular examination, retinal nerve fiber layer optical coherence tomography scan, and visual field tests performed in clinic, using OCCP and SAP. Within a week, participants were asked to repeat OCCP field test at home. 58 eyes of 29 healthy volunteers were selected. At the clinic, no difference between testing duration and fixation loss of SAP and OCCP was detected. False Positive (FP) rate of OCCP (3.57%) was significantly higher than SAP (1.07%, p < 0.001) while False Negative (FN) of SAP (1.64%) was significantly higher than those of OCCP (0.48%, p = 0.0225). In clinic OCCP compared to SAP revealed no significant difference in Mean Deviation (MD) (-0.29dB, p = 0.0825), and small differences in Pattern Standard Deviation (PSD) (-0.60dB, p = 0.0001) and Visual Index (VI)/Visual Field Index (VFI) (1.26%, p = 0.0199). Among 29 healthy participants, 15 people with 30 eyes completed home OCCP tests. Comparing in clinic and at-home OCCP, no significant difference between test duration, FP, FN, FL of was found. Small but significant improvements in OCCP MD (0.79dB, p = 0.0008), VI (1.63%, p = 0.0043), but not PSD (-0.45dB, p = 0.1609) were detected. Comparable outcomes between OCCP and SAP in clinic as well as between OCCP in clinic and OCCP at home were found in a normal Asian population.